2018
DOI: 10.1590/1678-992x-2016-0328
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of GSyV-1 and GLRaV-3 and prevalence of grapevine viruses in a grape-growing area

Abstract: ABSTRACT:The aims of this study were to determine the prevalence of viruses in 119 samples from 32 grapevine cultivars, collected from nine vineyards in a specific grape-growing area in southeastern Brazil, perform a partial molecular characterization of 14 isolates of Grapevine Syrah virus 1 (GSyV-1) and Grapevine leafroll-associated virus 3 (GLRaV-3) and assess the coat protein genetic variability of these viruses. The detection of viruses was implemented by realtime RT-PCR (reverse transcription polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…The virus GVB (ORF1 -replicase) had the higher π value (0.22880 ± 0.02406). The lowest π value was detected in GLRaV-3 coat protein gene (0.03846 ± 0.00780), consistent with previous work (Moura et al 2017). In general, the π values detected in this work are in accordance with π values found by other authors in studies involving viruses with DNA and RNA genomes (Garcia-Arenal et al 2001;Lima et al 2013;Zanardo et al 2014a;Moura et al 2017).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The virus GVB (ORF1 -replicase) had the higher π value (0.22880 ± 0.02406). The lowest π value was detected in GLRaV-3 coat protein gene (0.03846 ± 0.00780), consistent with previous work (Moura et al 2017). In general, the π values detected in this work are in accordance with π values found by other authors in studies involving viruses with DNA and RNA genomes (Garcia-Arenal et al 2001;Lima et al 2013;Zanardo et al 2014a;Moura et al 2017).…”
Section: Resultssupporting
confidence: 92%
“…GSyV-1 was first identified in USA (Al Rwahnih et al 2009) and symptoms include swollen graft unions, cracking and pitting of the wood, stem necrosis, leaf reddening and scorching, vine decline and death. Its presence has been reported in many countries (Glasa et al 2015) and was recently reported infecting vineyards in Brazil (Moura et al 2017). GVCV was found associated with leaf vein-clearing, shortening of the internodes, crinkled, misshapen and smaller leaves and reduced grape berry size, with irregular shape and abnormal texture (Guo et al 2014;Zhang et al 2011) and GRGV was previously reported in many viticultural countries (Beuve et al 2015).…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations